The relationship between mobile application and job performance among support staff in human resource department and administrative department at the Commission of the City of Kuching North (DBKU) / Muhammad Azim Norhisham - Norhisham, Muhammad Azim (2018)
The purpose of this research is to investigate the relationship between the use of mobile application and job performance. Back then people used email as a main communication tool to perform their daily task. But there are some difficulties occurs when using it. The reason why this problem not been solved yet is because of some people might not afford to buy smartphones or tablets and they have to rely on computers that has been provided by the organization. This study was carried out in Human Resource Management Department and Administrative Department at The Commission of the City of Kuching North. A number of 105 employees as the respondents took part in the survey and it was chosen randomly. Data was collected using questionnaire used for the study was adopted from Davis (1989) which is the technology Acceptance Model (TAM) and given a week time to complete the survey. Results revealed that the WhatsApp usage was widely used by the employees and they were competent in using the new technology as main a main tool to enhance their work performance. They possessed positive attitudes towards WhatsApp as it has a great experience and effective communication for the support staff. Finally, recommendations are made about using WhatsApp in the organization.